Studi Rencana Alat Pengukur Panas Pada Muai Logam - Ulul Ilmi (Universitas Islam Lamongan, 2019)
Measurement is the process of comparing measuring devices against measured objects. For measurement of magnitude, a measurement tool is needed. In this research activity, the object to be measured is the temperature at the metal expansion. To realize this goal, it is necessary to study the temperature measuring device on the metal expansion. The sensor used for temperature measuring devices is LM35 which is equipped by Arduino and LCD. Based on the test results obtained voltage values measured by a multimeter with an LCD display close to 100 percent or about 99.99 percent. With these results, it can be concluded that the temperature measurement meter is in accordance with the expected research objectives.